Cognitive Behavioral Therapy as an Adjunctive Treatment for Anxiety and Depression in Psoriasis Patients - Dewi, Dian Andriani Ratna; Wijayanti, Fakhira Ayu; Chen, Sissy; Firmansyah, Roby Syah Putra (Green Publisher Indonesia, 2023)
Psoriasis is a skin disease associated with the body's immune system. Mental health is one of the accompanying diseases of psoriasis. The clinical manifestations of psoriasis allow sufferers to experience anxiety and depression. There is a significant correlation between anxiety and depression to psoriasis, therefore, an adjunctive therapy is needed in addition to pharmacological therapy. One of these is Cognitive Behavioral Therapy (CBT), which aims to overcome anxiety and depression. This literature review summarizes recent findings regarding the application of CBT in psoriasis patients. The aim of this review is to summarize the latest findings about CBT as an alternative therapy in psoriasis patients. The literature review method was carried out by conducting literature reviews from various online databases, namely NCBI, Science Direct, Elsevier, and Mendeley using predetermined criteria. The results of the literature review showed that psoriasis causes severe psychological suffering, sadness, stigmatization, and decreased health-related quality of life. Result of this review is psychotherapy can lead to positive results in the development of a patient's condition. When performed regularly, CBT can effectively treat a variety of mental health conditions in individuals experiencing mild to moderate anxiety. CBT includes psychological training, self-monitoring, cognitive reconstruction, the prevention of exposure to negative stimuli, and rigorous training. The implications of writing this review are, CBT can be included in the treatment of psoriasis to obtain faster healing results through therapy methods for anxiety and depression in psoriasis patients.